Efektivitas Alat Pengolahan Limbah Domestik Rumah Tangga di Kecamatan Baruga Kota Kendari - Aditia, Arya; Assiddieq, Moch.; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2025)
Domestic household waste is waste generated from household activities. The type of domestic waste processed in this study is grey ater waste (washing and bathing waste). This study aims to design a wastewater treatment tool and test the effectiveness of the tool in reducing physical and chemical parameters, using an upflow filtration system with a combination of activated charcoal, silica sand, zeolite, manganese, and foam media. The processing procedure is carried out by flowing wastewater samples into pipes with variation of 600g activated charcoal, 600g silicasand, 600g zeolite, 600g manganese, and 10 cm of foam. The result shwed that domestic liquid waste after processing had a pH of 6, the watercolor became clear and odourless and TSS decreased by 70,43%.. The result of the tool’s effectiveness test show that the tool is effective in reducing pH, color parameters and TSS.. However, further research is needed on other parameters of domestic household waste.